VENUS meets SEMAT : How do they compare? - Geihs, Kurt (2014)
SEMAT (Software Engineering Methods And Theory) is an initiative to define a generic foundation for software engineering as a rigorous discipline. The so-called SEMAT kernel provides a thinking framework for software engineers that is not constrained to certain methods and processes but aims to encompass all kinds of proven principles and best practices. Our own interdisciplinary VENUS development method is designed to achieve similar generality and compatibility objectives, although the chosen application domain in VENUS has a much narrower scope. In this paper we compare the VENUS development method with SEMAT. The main contributions are positioning the VENUS development concepts within the SEMAT conceptual framework, and investigating whether SEMAT is an appropriate framework for dealing with inherently interdisciplinary development processes. In the end we present suggestions for the improvement of both approaches.